Superconductivity in Bi based Bi2PdPt. Issue 13 (25th May 2022) - Kataria, A.; Agarwal, T.; Sharma, S.; Singh, D.; Marik, S.; Singh, R. P.
Abstract : Single crystals of a new superconductor Bi2 PdPt have been synthesized and characterized by Laue diffraction, powder X-ray diffraction, and magnetic susceptibility and electrical/thermal transport measurements. Abstract : We report the synthesis and properties of superconducting Bi2 PdPt, a new member of the Bi–Pd based compounds that are known for simultaneous existence of topological surface states and superconductivity. It crystallizes in a hexagonal structure having space group P 63 / mmc . A detailed investigation of the properties via transport, magnetization and specific heat measurements confirms bulk superconductivity with a transition temperature, T C, of 4.0 (1) K in the moderate coupling limit.